Epidemiological Profile of Enteric Fever Cases Admitted In SCSMGH, Solapur - Malangori A. Parande; C. G. Patil; Madhavi V Rayate; Mehboob U Lukde (Medsci Publications, 2011)
Enteric fever, though occurs in all parts of the world, is a serious public - health problem in developing countries. It is one of the important causes of morbidity in India due to high rates of complications and hospitalization. This disease mainly affects the older children and young adults. So it's important to know the socio-demographic and other epidemiologic factors of the disease. The study was conducted with objectives to study socio-demographic and some of the epidemiologic features of enteric fever cases and also to study duration of hospital stay, outcome and mortality among enteric fever cases. A hospital based cross-sectional descriptive study was conducted in Solapur City from January 2002 to December 2002. All proved cases of enteric fever admitted in medicine and pediatric ward of SCSMGH, Solapur were the study subjects.   There was total 172 cases of enteric fever admitted during this period. Out of 172 enteric fever cases, majority (40.70%) were in the age group between 11-20 years. Males outnumbered the females giving M:F ratio of 1.6:1. A significant association was found between literacy status, socioeconomic status, levels of personal hygiene and occurrence of enteric fever. The overall duration of hospital stay ranged from 2 to 35 days with mean 7.91 days and S.D. 5.45 days. Fatality rate observed in this study was 1.74%. Thus, present study found majority of patients in 11-20 years (school children and adolescents) age group. There was significant association of literacy status, socioeconomic status and personal hygiene with development of enteric fever.